STUDY OF "INTERMEDIATE WORDS" IN THE NOUN AND ADJECTIVE WORD CLASS (Educator Insights: Journal of Teaching Theory and Practice, 2026)
This article highlights scientists who have conducted research on categories of words, and comments on the functional and semantic nature of intermediate words studied in two or more categories of words, including the expression of these words in the explanatory dictionary of the Uzbek language, on the relationship of words between nouns and adjectives to the category. done. The given theoretical information is explained by examples from the dictionary.